Corrosion Behaviour of Coatings on 304 Steel - Buyuksagis, Aysel; Ozturk, Ugur; Abbas Aksult, A. (Asian Journal of Chemistry, 2011)
The aim of this study is to determine the corrosion characteristics of 304 steel by the methods of Tafel extrapolation, linear polarization and electrochemical impedance spectroscopy (EIS). The steel surface is covered with nickel as electrochemical Watt's bath. Additionally, polyaniline (PANI) is synthesized on the steel electrode covered with nickel by the method of electrochemical cyclic voltammetry method. The effect of single and double coats of steel on corrosion resistance is examined in 3.5 % NaCl, 1N NaOH and 1N HCl solutions for the waiting time of 1, 48, 120 and 168 h. The surface morphology of steel, which is uncovered, is examined by SEM-EDX and the polyaniline is also examined in the same way. As well as the one covered with Ni + polyaniline is examined in the same way too. The synthesized polyaniline on the surface is analyzed by FTIR spectrum. Double coatings (Ni + polyaniline) has showed better corrosion resistance than single coating (polyaniline). Ni + polyaniline coatings in 1 N NaOH and 1 N HCl solutions has showed better corrosion resistance than polyaniline coating. The corrosion current of the steel covered with Ni + polyaniline in 1 N HCl and 1 N NaOH solutions is lower than the corrosion current of polyaniline coating. SEM-EDX analyses have showed that the surface covered with Ni + polyaniline is more homogenous and compact. This result is also convenient with the electrochemical experiment results.